Body in sacred-erotic literature: an example in Vita Nuova, by Dante Alighieri, and in the testimony of the transverberation of Saint Teresa D'Ávila - Cavallari, Doris Natia [UNESP] (2023)
Medieval literature developed between 1200 and 1350 and its subsequent evolution revealed a period of great richness in mystical literary production, according to scholars of the history of Western mysticism, such as Bernard McGinn (1998). The period is highly propitious for a preliminary investigation in which mysticism is the protagonist and, for this reason, we propose to study the concept of spiritual eroticism in excerpts from Vita Nuova (1292-1293) , by Dante Alighieri (1265-1321) , poet, philosopher, politician and great name in Italian literature, and in the writings of Saint Teresa D'avila (1515-1582), blessed, author of treatises, poems and one of the most important mystical wives of the Catholic Church. We start from the hypothesis that the erotic charge present in the mystical experience goes beyond just an ideal of bodily pleasure, but presents, through the body, the beginning and signs of the magnitude of spiritual experimentation. To this end, in Dante we will observe the effects of this mystical experience on the body, based on the studies of Agamben (2007), such as the concept of love as a ghost, Sturges (2012) and Santagata (2017), as well as exploring the mystical and erotic theme of Santa Teresa through her own writings regarding the episode of her transverberation and the treatises by Camara (2020) and Alves (2019).